ANALISIS KOMPREHENSIF AYAT MUHKAM DAN MUTASYABIH DALAM AL-QUR’AN: KAJIAN KONSEPTUAL, LINGUISTIK, DAN IMPLIKASI PENAFSIRAN - Mauizah; Noor Eliyen; Azkia; Edy Surianto; Akhmad Dasuki (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study examines the concepts of muhkam and mutashabih verses in the Qur’an as essential components of Ulumul Qur’an (Qur’anic sciences). The background of this study arises from the need to understand the characteristics of Qur’anic verses accurately, given the diversity of linguistic styles and the depth of meanings contained within them. The study aims to explain the definitions, characteristics, examples, and functions of muhkam and mutashabih verses, as well as the wisdom behind their existence. The research employs a literature review method by analyzing classical and contemporary works on Qur’anic studies, scientific journals, and primary material from ULUMUL QUR’AN Kelompok 7. The findings indicate that muhkam verses have clear meanings and serve as the foundation of Islamic law, while mutashabih verses contain ambiguous, symbolic, or metaphysical meanings that require interpretation. Both categories complement each other within the structure of the Qur’an and reflect its miraculous nature. This study highlights the importance of methodological accuracy in interpreting Qur’anic verses to prevent misinterpretation and doctrinal deviation.